An excellent lecturer from students' perspectives: a study on two universities / Roslina Ab Wahid - Ab Wahid, Roslina (Institute of Quality & Knowledge Advancement (InQKA), 2005)
The quest for quality seems an endless journey to many, especially for those in the service industry. As customer needs and wants change over time, service providers are kept wondering what is it that customers want now and in the near future so that they can plan for and design the service that would satisfy the customers. This paper identifies an excellent lecturer from the students' point of view based on a quality perspective. Studies were conducted on two universities, one in the United Kingdom and the other in Malaysia asking students to rank order attributes they expect of an excellent lecturer. Findings from both studies reveal that the top five most important attributes of an excellent lecturer are competence, communication, reliability, responsiveness, and understanding, in that order. Hopefully, the above findings would be used by both lecturers and universities as service providers to minimize the gap between students' expectations and the service providers' perceptions, thus enhancing students' satisfaction. The researcher concludes that controlling and measuring quality in higher education is not an easy task due to high customer contacts and interactions during service delivery which makes quality not only the sole responsibility of the service provider, but also of the customer. However, it is not totally impossible.